2011
DOI: 10.4025/actasciagron.v33i3.6018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methodologies for degree-day estimation using numerical methods

Abstract: The development of projects related to the yield of various crops has been greatly eiihaticcd with the incorporation of mathematical models as well as essential and more consistent equations which enable a prediction and greater approximation to their actual behavior, thus reducing error in estimate. Among the operations requiring further investigation are those related to crop growth, characterized by the ideal temperature for addition of dry matter. Due to the wide use of mathematical methods for representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
6
0
3
Order By: Relevance
“…Souza et al (2011) estimated the annual degree-days availability for cane sugar in Botucatu (SP), and observed that a DD2 similar method using the averages calculated from daily maximum and minimum temperatures produced estimations of degree-days accumulation similar to those obtained from Villa Nova et al (1972) method. Furthermore, when the authors used integration methods from temperatures taken hourly the lowest estimates of degree-days accumulation were obtained, as reported in the present study.…”
Section: Discussionmentioning
confidence: 72%
“…Souza et al (2011) estimated the annual degree-days availability for cane sugar in Botucatu (SP), and observed that a DD2 similar method using the averages calculated from daily maximum and minimum temperatures produced estimations of degree-days accumulation similar to those obtained from Villa Nova et al (1972) method. Furthermore, when the authors used integration methods from temperatures taken hourly the lowest estimates of degree-days accumulation were obtained, as reported in the present study.…”
Section: Discussionmentioning
confidence: 72%
“…This behavior is often expected since the degree-days method assumes a linear link between temperature and plant development; however, such connotation is only true into the cardinal temperature range of the plant -minimum base temperature Tb; optimum temperature -Topt; and maximum base temperature TB (Fagundes et al, 2010;Cardoso, 2011;Souza et al, 2011). The coefficient of variation (CV %) could be used to measure the duration variability (days or degree days) on the developmental phases of cultures grown at different times (Cardoso, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The minimum (Tb) and maximum (TB) basal temperatures of 12 and 35 °C respectively (Mota et al, 1977), were used to find the thermal sums (accumulated degree days, GDD) for squash. The proposal by Ometto (1981) was adopted due to cases that were seen as possible, depending on the local weather conditions, as it was recommended by Souza et al (2011). The experiment was conducted in randomized blocks with six treatments (sowing epochs with ten-days intervals in winter, on June 05, 15 th , 25 th , and July 05, 15 th , 25 th of 2013) and four repetitions of five plants each.…”
Section: Methodsmentioning
confidence: 99%
“…The minimum (Tb) and maximum (TB) basal temperatures of 14 and 36°C (Nowbuth and Pearson, 1998) were applied in order to find the thermal sums (accumulated degree-days) for cauliflower plants. The proposal by Ometto (1981) was applied to cases suitable for it which depends on the local weather conditions, according to Souza et al (2011b).…”
Section: Yearmentioning
confidence: 99%